Pengembangan E-Book Pekerjaan Dasar Elektromekanik Berbasis Student Facilitator and Explaining - April Muhshanah; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research is based on the background of learning media for Electromechanical Basic Work subjects that are still minimal and the learning model used is still teacher-centered. This study aims to develop an e-book of Electromechanical Basic Work subjects using the student facilitator and explaining a learning model that is valid, practical and effective. This type of research is a development research method (Research and Development). The method used is the 4-D model which consists of defining (Define), designing (Design), developing (Development), and disseminating (Disseminate) stages. The research subjects were students of class X TITL SMK Negeri 1 Kerinci. Data collection techniques use evaluation sheets in the form of questionnaires for validity and practicality data, while objective tests are used for effective data. The results showed that (1) the validity test of the Electromechanical Basic Work e-book using the SFAE learning model had been checked and declared valid. (2) the practicality test of the Electromechanical Basic Work e-book using the SFAE learning model has been checked and declared practical. (3) the effectiveness test of the Electromechanical Basic Work e-book using the SFAE learning model has been checked and declared effective. It can be concluded that the e-book of Electromechanical Basic Work subjects based on the student facilitator and explaining learning model is worth distributing because it has been declared valid, practical, and effective.